Beschreibung einer neuen Gattung der Familie Scirtidae aus der Orientalischen Region (Coleoptera)(144. Beitrag zur Kenntnis der Scirtidae). - Klausnitzer, Bernhard (Contributions to Entomology = Beiträge zur Entomologie, 2009)
The species of the genus Cyphon Paykull, 1799, hitherto treated as Cyphon chlorizans group, are combined in the genus Ypsiloncyphon gen. n. The new genus is characterized by derived structures of the tegmen, the 9th sternite and 8th and 9th tergite of the male as well as the 8th sternite of the female. A determination key of all known species and a catalogue with the new combinations are provided. Keywords Coleoptera, Scirtidae, Ypsiloncyphon, Cyphon, new genus, Orientalis, Paläarktis. Nomenclatural Acts Ypsiloncyphon Klausnitzer, 2009 (Scirtidae), gen. n. amami (Yoshitomi, 2005) (Ypsiloncyphon), comb. n. hitherto Cyphon amami chlorizans (Klausnitzer, 1973) (Ypsiloncyphon), comb. n. hitherto Cyphon chlorizans formosus (Klausnitzer, 1980) (Ypsiloncyphon), comb. n. hitherto Cyphon formosus hofferi (Klausnitzer, 1973) (Ypsiloncyphon), comb. n. hitherto Cyphon hofferi honshuanus (Yoshitomi, 2005) (Ypsiloncyphon), comb. n. hitherto Cyphon honshuanus jaloszynskii (Ruta, 2004) (Ypsiloncyphon), comb. n. hitherto Cyphon jaloszynskii jiangxiensis (Yoshitomi, 2005) (Ypsiloncyphon), comb. n. hitherto Cyphon jiangxiensis karnatakaensis (Ruta, 2007) (Ypsiloncyphon), comb. n. hitherto Cyphon karnatakaensis kejvali (Ruta, 2007) (Ypsiloncyphon), comb. n. hitherto Cyphon kejvali luteoapicalis (Ruta, 2007) (Ypsiloncyphon), comb. n. hitherto Cyphon luteoapicalis maharashtraensis (Ruta, 2007) (Ypsiloncyphon), comb. n. hitherto Cyphon maharashtraensis mahensis (Champion, 1924) (Ypsiloncyphon), comb. n. hitherto Cyphon mahensis mendosus (Klausnitzer, 1980) (Ypsiloncyphon), comb. n. hitherto Cyphon mendosus micans (Klausnitzer, 1973) (Ypsiloncyphon), comb. n. hitherto Cyphon micans minutulus (Klausnitzer, 1980) (Ypsiloncyphon), comb. n. hitherto Cyphon minutulus nigroflavus (Ruta, 2004) (Ypsiloncyphon), comb. n. hitherto Cyphon nigroflavus okinawanus (Yoshitomi, 2005) (Ypsiloncyphon), comb. n. hitherto Cyphon okinawanus paramicans (Klausnitzer, 1979) (Ypsiloncyphon), comb. n. hitherto Cyphon paramicans pseudoatratus (Ruta, 2007) (Ypsiloncyphon), comb. n. hitherto Cyphon pseudoatratus reconditus (Klausnitzer, 1980) (Ypsiloncyphon), comb. n. hitherto Cyphon reconditus sinuosus (Sasagawa, 1985) (Ypsiloncyphon), comb. n. hitherto Cyphon sinuosus spinifer (Yoshitomi, 2005) (Ypsiloncyphon), comb. n. hitherto Cyphon spinifer tamilensis (Ruta, 2007) (Ypsiloncyphon), comb. n. hitherto Cyphon tamilensis voluptificus (Klausnitzer, 1980) (Ypsiloncyphon), comb. n. hitherto Cyphon voluptificus yayeyamanus (Yoshitomi, 2005) (Ypsiloncyphon), comb. n. hitherto Cyphon yayeyamanus